The Food Police: Food Stamps, Surveillance, and the Construction of the Undeserving Hungry - (:unkn) unknown (My University, 2021)
Hunger in America is produced through broader social and economic inequality and patterns of hunger are unevenly distributed across places and social groups. While 10.5% of all U.S. households experienced hunger, Black households, Latino households, households with children headed by either a single woman or a single man, and households in poverty faced substantially higher rates of hunger in 2019 (Coleman-Jensen et al. 2020). The Food Stamp Program (FSP), now called the Supplemental Nutrition Assistance Program (SNAP), is the largest hunger relief program in the U.S. Acknowledging the racialized and gendered patterns of hunger in the U.S. is central to my research, yet federal policy and hunger debates rarely directly address the inequitable distribution of hunger. Drawing from more than 100 congressional hearings between 2000 and 2018 that were related to the reauthorization of FSP and SNAP, I examined the rhetoric and dominant ways of understanding hunger that informed the production of federal hunger relief policy in this period. I ground my examination of legislative discourses about hunger within shifting dynamics of race, class, and gender in the United States, and my discourse analysis interrogates the logics and rhetoric shaping post-welfare reform shifts in debate on FSP and SNAP policy. This dissertation documents an erosion of the federal commitment to hunger relief in the United States during this timeframe. My analysis demonstrates how after welfare reform, legislative debates on federal hunger relief became increasingly focused on disciplining what I term, drawing from Katz’s (1989) critical work on poverty, the “undeserving hungry.” Examining legislative debates about hunger is critically important as widely circulated understandings of hunger shape federal anti-hunger policies in ways that determine access to the life sustaining resource of food for some of the country’s most vulnerable populations. In this way, discourses about hunger directly connect to questions of well-being and life and death. I examine the eroding commitment to hunger relief within neoliberal discourses about austerity and personal responsibly and in legislative discourses that construct SNAP recipients as dependent, obese, or criminal. Instead of focusing on hunger itself, much of the legislative debate scrutinizes the everyday lives of the poor and hungry: examining their purchases, where they shopped, and whether they made “good” choices. At the same time, my analysis of legislative debates reveals that there was never an assessment as to whether the implementation of new disciplinary measures actually reduced hunger or created cost-savings. Rather, legislators questioned whether we really need SNAP, citing unsubstantiated high rates of waste, fraud, and abuse (Chapters 3 & 5) and uncritical and paternalistic analyses of obesity (Chapter 4). Discourses contrasting the (non-white) ‘undeserving hungry’ against the hardworking (white) taxpayer supported the creation of new exclusionary boundaries around SNAP and (re)produced racialized and gendered assumptions about the poor, deemed dependent, obese, criminal, or incapable of making healthy food choices.
Keywords: Classism; Food Stamps; Health Equity; Hunger; Racism; Sexism